(untitled) (Ameghiniana, 2014)
Nuia sibirica Maslov associated with clasts containing tangled Girvanella tubes occurs in grainstones through the Cambrian-Ordovician boundary in a locality previously regarded as part of western Gondwana, belonging to the Famatina System (Lower Member of the Volcancito Forrnation), in northwestern Argentina. Known records of Nuia and Girvanella in the Gondwanan continents come from Arenig limestones of the Precordillera terrane, now regarded as an exotic terrane derived from Laurentia, and from Australia (Eastern Gondwana). The present paper provides a detailed description of these organisms together with an in-depth paleoenvironmental-paleoecologic discussion. The organic nature of Nuia is suggested based on its morphological variety and internal structure. Both algae (although Nuia is not strictly regarded as such) are presently considered as typical low-latitude carbonate setting inhabitants, and as such, their occurrence in this region of Gondwana is not in agreement with existing paleogeographic and geodynamic interpretations. Low-latitude paleoclimatic and paleogeographic alternatives are discussed in the light of this discovery.